1997
DOI: 10.1002/(sici)1097-4628(19970808)65:6<1113::aid-app6>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Water-alcohol separation by pervaporation through poly(amide-sulfonamide)s (PASAs) membranes

Abstract: Pervaporation membranes derived from seven homopolymers of poly(amide-sulfonamide)s (PASAs) were prepared by casting 10-17% polymer solutions of N,N-dimethylacetamide. The membranes were characterized by sorption experiments, scanning electron microscope, and wide-angle X-ray diffraction. During the pervaporation of 90 wt % aqueous solution of methanol, ethanol, 1-propanol, and 2-propanol, all membranes were preferentially permeable to water, and their separation factors were mainly dependent on the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This can be attributed to the increase in molecular diffusivity and the reduction in flow viscosity at the higher temperature. Similar observations have been reported by Jiraratananon et al 12 and Chan et al 13 To better quantify the dependence of the mass transfer resistance on temperature, the collected permeate flux data at different temperatures were used to calculate the activation energy for water according to the Arrhenius relationship:…”
Section: Effects Of Feed Temperature On Water Fluxmentioning
confidence: 65%
“…This can be attributed to the increase in molecular diffusivity and the reduction in flow viscosity at the higher temperature. Similar observations have been reported by Jiraratananon et al 12 and Chan et al 13 To better quantify the dependence of the mass transfer resistance on temperature, the collected permeate flux data at different temperatures were used to calculate the activation energy for water according to the Arrhenius relationship:…”
Section: Effects Of Feed Temperature On Water Fluxmentioning
confidence: 65%
“…It has been reported that as the molecular weight of permeated molecules in a given homologous series increases, the permeation flux decreases, and the separation increases. 13,14 In this study the membrane selectivity in pervaporation of aqueous organic mixtures increases in the order of acetic Ͻ ethanol Ͻ 2-ethoxyethanol without sacrificing the permeation rate, depending on the feed composition. Figure 6 shows the effect of temperature and feed concentration on pervaporation membrane performance for acetic acid-water mixtures.…”
Section: Pervaporation Performance For Organic-water Mixturesmentioning
confidence: 83%
“…There is a possibility to modulate the properties of the membranes using volume and surface modifications. The most commonly used membrane polymer materials for pervaporation dehydration are polyvinyl alcohol [ 13 , 14 ], polyamides and polyimides [ 15 , 16 , 17 , 18 , 19 ], polysulfone [ 20 , 21 , 22 ], polyacrylonitrile [ 23 , 24 ], chitosan [ 25 , 26 , 27 ], and aromatic polymers (e.g., polybenzoxazole and polybenzimidazole) [ 28 , 29 ], etc. These membranes are often modified by blending with other polymers [ 30 , 31 ], modifying with various reagents [ 32 ], and cross-linking by different methods [ 2 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%